Organismal and Molecular Malacology 2017
DOI: 10.5772/67847
|View full text |Cite
|
Sign up to set email alerts
|

Possible Poecilogony Due to Discontinuous Multifactorial Inheritance in Some Mediterranean Species of Raphitoma (Mollusca, Conoidea, Raphitomidae)

Abstract: At least 10 pairs of similar, most probably closely related, species of Raphitoma are often sampled in the same Mediterranean localities. In each pair, one member bears a planktotrophic protoconch and the other a lecithotrophic one. We propose that the phenomenon may be attributed to a simple gene that functions in conjunction with others and environmental factors to exhibit a discontinuous multifactorial inheritance leading to poecilogony. Below a threshold, the animals may produce fewer and larger germ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Later on, Cachia, Mifsud, and Sammut (2001) contributed to the knowledge of the Mediterranean Raphitoma species and reported 14 taxa from Maltese Islands, with their descriptive and distributional features. Recently, the Raphitoma species distributed along the Greek Seas have been subjected by Manousis, Kontadakis, Mbazios, Polyzoulis, and Galinou-Mitsoudi (2017) and Manousis, Kontadakis, Mbazios, and Polyzoulis (2018). In the last study were reported 27 species from the Greek coasts.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Cachia, Mifsud, and Sammut (2001) contributed to the knowledge of the Mediterranean Raphitoma species and reported 14 taxa from Maltese Islands, with their descriptive and distributional features. Recently, the Raphitoma species distributed along the Greek Seas have been subjected by Manousis, Kontadakis, Mbazios, Polyzoulis, and Galinou-Mitsoudi (2017) and Manousis, Kontadakis, Mbazios, and Polyzoulis (2018). In the last study were reported 27 species from the Greek coasts.…”
Section: Introductionmentioning
confidence: 99%